2019
DOI: 10.1155/2019/7250838
|View full text |Cite
|
Sign up to set email alerts
|

Towards New Approaches to Evaluate Dynamic Mosaicism in Ring Chromosome 13 Syndrome

Abstract: Individuals with ring chromosome 13 may show characteristics observed in a deletion syndrome and could present a set of dismorphies along with intellectual disability, according to chromosomal segments involved in the genetic imbalance. Nevertheless, ring anomalies likewise is called “dynamic mosaicism”, phenomena triggered by the inner instability concerning the ring structure, thus leading to the establishment of different cell clones with secondary aberrations. Phenotypic features, such as growth failure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A comparable finding was reported in a case of r(13), with 1% of micronucleated cells and 40% of these MN containing sequences derived from chromosome 13 [ 20 ]. Petter et al [ 21 ] also found MN in three cases of r(13); all exhibiting chromosome 13 signals, as confirmed by WCP13. These findings support the hypothesis that the structure of ring chromosomes inherently leads to their exclusion from the main nucleus as MN.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A comparable finding was reported in a case of r(13), with 1% of micronucleated cells and 40% of these MN containing sequences derived from chromosome 13 [ 20 ]. Petter et al [ 21 ] also found MN in three cases of r(13); all exhibiting chromosome 13 signals, as confirmed by WCP13. These findings support the hypothesis that the structure of ring chromosomes inherently leads to their exclusion from the main nucleus as MN.…”
Section: Discussionmentioning
confidence: 65%
“…In conclusion, ring chromosome syndrome is a pathological entity with significant variability due to factors including the affected chromosome, gene loss, positional effects of genes near breakpoints, and unbalanced segregation following ring chromosome sister chromatid exchange. Although previous work has suggested instability associated with chromosome rings, the evidence has been inconclusive [ 15 21 ]. Remarkably, we have demonstrated an instability of the r(14) chromosome, mainly involving anaphasic lags and its exclusion from the nucleus in the form of a micronucleus.…”
Section: Discussionmentioning
confidence: 99%
“…While we assessed an intentionally diverse set of rearrangements, future application of our methods to larger sets of specific rearrangement types (and with T2T references beyond a single haploid assembly) is poised to contribute answers to additional long-standing questions about their formation and biology, for example: the preference for certain chromosomes in Robertsonian translocations 52,53 ; the properties of fused or dicentric centromeres 52,60 ; the frequency of fusion genes/enhancer swapping; position effects on gene expression [61][62][63][64] ; and the biology of subsequent mitotic/meiotic errors (i.e. "tissue-specific dynamic mosaicism") 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to variations in chromosomal regions implicated in genetic imbalance, r(13) may manifest with a variety of dysmorphic features as well as intellectual impairments. 6 The different phenotype of the patients with r(13) is not only associated with large deletions of the q arm of chromosome 13 but also related to several factors such as mosaicism of the ring chromosome. Ring abnormalities are sometimes referred to as "dynamic mosaicism," a phenomenon caused by internal instability in the ring structure, which results in the formation of distinct cell clones with secondary chromosomal aberrations.…”
Section: Discussionmentioning
confidence: 99%